Synthesis and characterization of lactic acid-magnesium oxide nanocomposites: how nanoparticle size and shape effects polymerization and the resulting properties of the polymer - Beavers, Erin M. (Kansas State University, 2008)
In this study, low molecular weight nanocomposites of L-lactic acid were synthesized with Commercial, Nanoactive®, and Nanoactive Magnesium Oxide Plus®, each of which differs in both surface area and shape. Synthesis of the composites was carried out by refluxing the nanoparticles in a solvent suspension. Both methanol and 1-propanol were used during this work. Heating was necessary in order to achieve adequate dispersion of the particles before adding L-lactic acid. Upon addition of the lactic acid monomer, the reactants were refluxed for a total of 3 hours, followed by evaporation of the excess solvent. The products were characterized via DSC, TGA, FTIR, [superscript]1H and [superscript]13C NMR, UV-Vis, XRD, and TEM. Additionally, titrations were performed with the reactants to ensure the particles were not being consumed by the acid regardless of their size. The results of this study indicate that condensation reactions are the primary polymerization route of lactic acid and polymerization appears to initiate on the surface of the magnesium oxide particles, resulting in physically unique composites of lactic acid and magnesium oxide.
Keywords: Lactic Acid; Magnesium Oxide; Nanocomposites; Chemistry, Inorganic (0488)